What Drives Organizations to Start a Cross-sector Partnership? A Review on Typologies and Dimensions - Sharafi Farzad, Fatemeh; Amran, Azlan; Salamzadeh, Yashar; Hafezalkotob, Ashkan (Journal of Entrepreneurship, Business and Economics, 2021)
Due to the importance of cross-sector partnerships (CSPs) in today’s world on the one hand and the diversity of the research done in this field, a need for comprehensive frameworks about this practical phenomenon is felt. The main purpose of this paper is to provide a comprehensive view about drivers of cross-sector partnership to help all actors from government, business, and nonprofit sectors to recognize the big picture of the initial stage of a successful CSP. Although this paper is not a pure literature review article, but a literature review is used as a tool to find all relevant factors which influence starting a CSP. This paper categorizes all these factors into five types of drivers and motives, including main drivers, secondary drivers, partner selection drivers, organizational factors, and contextual factors. Proposing the above-mentioned framework for CSPs drivers is the main novelty of the current paper, and due to its potential to be used both in academia and practices related to CSPs, this framework can be the starting point for many other research policy-making initiatives. On the other hand, CSP partners can also use it to make wiser decisions on building a partnership with other sectors. Research paper Keywords: Cross-Sector Partnership; Typologies; Drivers of Partnership; Partner Selection; Cross-Sector Partnerships’ Antecedents Reference to this paper should be made as follows: Sharafi Farzad, F., Amran, A., Salamzadeh, Y., & Hafezolkotob, A. (2021). What drives organizations to start a cross-sector partnership? A review on typologies and dimensions. Journal of Entrepreneurship, Business and Economics , 9 (1), 121–162.